WAKTU PENYERAPAN MAKSIMUM KITOSAN DARI CANGKANG BELANGKAS DENGAN MEGGUNAKAN KARAKTERISASI SEM - Masdania Zurairah Siregar (Bajang Institute, 2022)
Research has been carried out on the maximum absorption time of horseradish chitosan as an adsorbent for Hg metal. Next, the characterization of chitosan was carried out using SEM. The maximum flow time was fixed at 5 mL/minute, while the contact time between the adsorbent and the Hg sample was varied at 5,10, 15, 20, and 25 minutes. The results obtained that the maximum contact time between the chitosan adsorbent and the Hg sample was 25 minutes with a yield of 83.27%.